2014
DOI: 10.1038/nchembio.1718
|View full text |Cite
|
Sign up to set email alerts
|

De novo biosynthesis of terminal alkyne-labeled natural products

Abstract: Abstract:The terminal alkyne is a functionality widely used in organic synthesis, pharmaceutical science, material science, and bioorthogonal chemistry. This functionality is also found in acetylenic natural products, but the underlying biosynthetic pathways for its formation are not well understood. Here we report the characterization of the first carrier proteindependent terminal alkyne biosynthetic machinery in microbes. We further demonstrate that this enzymatic machinery can be exploited for the in situ g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 43 publications
2
121
0
1
Order By: Relevance
“…With the dihalotryptophans in hand, we decided to explore the possibility of using this reaction to process an alkynyl indole (Scheme 3). Incorporation of an alkyne "tag" into a small molecule, protein or natural product can enable selective diversification and tagging, 12 through an alkyneazide cycloaddition reaction, commonly known as "click chemistry". 13 We wanted to see if alkyne-substituted indoles were amenable to the tryptophan synthase reaction.…”
Section: Tryptophan Synthasementioning
confidence: 99%
“…With the dihalotryptophans in hand, we decided to explore the possibility of using this reaction to process an alkynyl indole (Scheme 3). Incorporation of an alkyne "tag" into a small molecule, protein or natural product can enable selective diversification and tagging, 12 through an alkyneazide cycloaddition reaction, commonly known as "click chemistry". 13 We wanted to see if alkyne-substituted indoles were amenable to the tryptophan synthase reaction.…”
Section: Tryptophan Synthasementioning
confidence: 99%
“…Especially, investigation of traditional oriental medicines will propose many more novel natural product targets for microbial production. [290] Moreover, with novel enzymes being uncovered, such as the ones in charge of 4+2 cyclic reaction [291] and alkyne biosynthesis, [292] discovery and production of novel natural compounds by metabolic engineering has been greatly facilitated. Overall, cumulated systems biological techniques with recently being developed innovative engineering tools would greatly accelerate this field of research with the objective of providing invaluable natural compounds efficiently.…”
Section: Perspectivesmentioning
confidence: 99%
“…Following subsequent extension, presumably via primary metabolic fatty acid synthase (FAS), and conversion into the malonate derivative via AntE (see below), 5-hexynoylmalonyl-CoA was incorporated into an antimycin analogue ( 19 ) as an extender unit (Figure 3D(ii)). 24 This result paves the way to utilizing this trio of genes to generate “taggable” polyketides without the need for the feeding of alkyne precursors.…”
Section: Polyketide Starter Unitsmentioning
confidence: 96%
“…Following this, JamB desaturates the terminal alkene of 18 to yield the alkyne 16 , which is used to prime the PKS (Figure 3D(i)). 24 In vitro investigations suggested that JamB does not exhibit much substrate tolerance. When challenged with alkenoyl-JamC thioesters of varying length (5 to 8 carbons) conversion to the corresponding alkynoyl-JamC was only observed for 16 .…”
Section: Polyketide Starter Unitsmentioning
confidence: 99%
See 1 more Smart Citation